Cybernetic security of the state: characteristic features & problem aspects - КОРЧЕНКО, Олександр Григорович; БУРЯЧОК, Володимир Леонідович; ГНАТЮК, Сергій Олександрович (Ukrainian Scientific Journal of Information Security, 2013)
Recently the problem of cybernetic space of the state security arises sufficiently acute. This problem is particularly important in areas where a large quantity of critical information is circulating (e.g. in civil aviation). In this context in the paper the characteristic features of the state cybersecurity were defined and the problems of cybernetic security of Ukraine were analyzed. In addition, the actual problems of civil aviation cybersecurity and their possible solutions were given. The practical recommendation to provide cybernetic security of civil aviation and whole cyberspace of Ukraine were also formulated.